Analisis Kekuatan Material pada Poros Kemudi Kapal Tradisional di Kabupaten Rembang Jawa Tengah - Eva Hertnacahyani Herraprastanti; Hendri Suryanto; Helmi Gunawan; Retno Wahyusari (Jurnal Energi Dan Manufaktur, 2023)
Central Java Province, especially Rembang Regency, has great potential for marine resources. However, based on PRDB data for the fisheries sub-sector, from 2010 to 2021 the fishery sector has slowed down. One of the reasons for this condition is that fishermen in Rembang Regency still use small-scale capture fisheries methods. Alternative fishing patterns need to be considered to increase capture fisheries production and reduce ship fuel costs so that fishing operations can remain profitable. One way that can be done is by conducting a study on the ship's steering axis. The traditional ship steering axle uses AISI 1045 material which is hard, wear-resistant, torsional-resistant, and quite ductile at the core. This study aims to analyze the strength of the material on the steering shaft of a traditional ship using Solidworks. The method used is a quantitative simulation to analyze the strength of the structure on the steering shaft of a traditional ship including the strength of the structure, the magnitude of the force, the torque and the stress that occurs. This analysis will be useful to assist fishermen in selecting suitable materials for traditional boats. The result of this research is AISI 1045 material has a yield strength of 5.3e+08 N/m2. The traditional ship's steering axis when given a bending load of 100 N, with a torque of 10 N.m, the maximum stress is 33.64 N/mm2, so the safety factor is 5.588585. The critical stress will occur when the bending load is increased to 600 N and the torque is 60 N.m, the maximum stress is 201.9 N/mm2 and the safety factor is less than 1, which is 0.931154. The maximum stress obtained exceeds the maximum stress required by the Indonesian Classification Bureau (BKI) which is 188 N/mm2 so that the construction is said to be unsafe.